Understanding Defense Industry: A Systems Thinking Perspective - Ozdemir, Mehmet Hilmi; Ozkan, Gokhan (Perceptions (Ankara, Turkey), 2021)
The defense industry can be thought of as a complex system of intense interactions between humans and high-tech machines, platforms and data systems with a large number of dynamically interacting variables. Within the defense industry, many complex decision-making processes take place, in which even very intelligent and highly educated people often make poor decisions due to failure to grasp this complex system as a whole, and/or by using linear or deterministic methods. The present study is structured to offer decision-makers, researchers and practitioners dealing with defense industry subjects new perspectives. The development of new mental models requires new perceptions and even confrontations between different perceptions. The most distinctive developments begin with creative ideas that are the outcomes of particular mental models. The defense industry is among those that continuously seek innovative approaches, creative ideas and new solutions. A systems thinking approach, together with Viable Systems Model (VSM) and system dynamics methodologies is one such innovative approach. One successful application of systems thinking--NATO's Aggregated Resilience Model--can be considered a benchmark in the development of new mental models and creative solutions. The inevitable decision support needed by policy- and decision-makers who pursue innovation in the defense industry can be met by the "systems thinking" approach discussed in this article. Keywords Defense industry, systems thinking, complexity, system dynamics, viable systems model, mental models, modeling and simulation.